Quantifying and Comparing Bipolar Versus Freehand Flake Morphologies, Production Currencies, and Reduction Energetics During Lithic Miniaturization. (3rd July 2017) - Pargeter, Justin; Eren, Metin I.
ABSTRACT: Recognized by archaeologists for over a century, and practiced by hominins in nearly every archaeological context in which flaked stone is used, bipolar technology involves the coordination of at least three components (hammer, anvil, and core). Archaeologists are increasingly aware of the variability within bipolar reduction, such that it can hardly be considered a single unified reduction strategy. Our experiments investigate the role of axial bipolar reduction versus freehand reduction as strategies for lithic miniaturization on flint. The results provide clear, probabilistic, and quantifiable methods for identifying bipolar reduction in archaeological assemblages. They also show the time and energetic benefits of bipolar reduction over freehand reduction in contexts involving small, elongated flake production. Our results have wide applicability for interpreting archaeological assemblages across Africa, Europe, North America, and Australia.